Empowering Santri Through Ecoenzyme Waste Management And Traditional Jamu: A Community Service Program At Darul Falah Putri Islamic Boarding School, Barito Kuala - Nily Su'aida; RR Ariessanti Alicia Kusuma Wardhani; Yeni Riza; Budianti Soemarie (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Environmental sanitation issues and low immunity levels among students remain major challenges in Islamic boarding schools located in rural swamp areas. This community service program, funded by the Ministry of Higher Education, Science, and Technology (Kemdiktisaintek) through the BIMA Grant Scheme, aimed to address these problems at Darul Falah Putri Islamic Boarding School, Barito Kuala. The activities consisted of (1) counseling and training on household waste management through ecoenzyme production, and (2) counseling and training on the utilization of Family Medicinal Plants (TOGA) for traditional jamu preparation as an immune booster. Methods included interactive lectures, group discussions, practical demonstrations, and evaluations through pre-tests and post-tests. The results showed a significant increase in students’ knowledge and skills, with average test scores improving from 75 to 90 for ecoenzyme training and from 70 to 85 for jamu preparation. Students successfully produced ecoenzyme fermentation products and ready-to-drink herbal jamu, demonstrating the applicability of local wisdom in promoting health and sustainability. This program not only enhanced students’ awareness and competencies but also contributed to fostering a culture of healthy living and environmental responsibility within the pesantren community.